A Study on the Relationships between Elementary School Principal’s Positive Leadership and Teacher’s Organizational Citizenship Behavior in Remote Area in Taiwan - FAN, Chih-Wen; Hsieh, Wu-Mei (Advances in Social Sciences Research Journal, 2021)
The aim of this study was to investigate the current state and related situations of the relationship between principal’s positive leadership and teacher’s organizational citizenship behavior of elementary schools in Hualien County. This study adopted questionnaire survey, using stratified random sampling to select 347 public elementary teachers in Hualien County. The research tool was the “Questionnaire of the Relationship between principal’s positive leadership and Teacher’s organizational citizenship behavior of elementary schools” adapted by the study. A total of 326 valid questionnaires were collected, with the effective recovery rate 93.9%. The data obtained were analyzed and tested with descriptive statistics, t-tests, one-way analysis of variance, product moment correlation, and multiple regression analysis. The following conclusions were reached. 1.The overall current situation of principal’s positive leadership and teacher’s organizational citizenship behavior of elementary schools was good. 2.Principal’s Positive Leadership and Teacher’s organizational citizenship behavior of elementary schools was significantly positively related. Principal’s Positive Leadership of elementary schools could effectively predict Teacher’s Organizational Citizenship Behavior. Finally, based on those findings, the study suggests some implications of administrative authorities, elementary school principals, teachers, and further studies as well